The Meaning and Essence of the Islamic Education Curriculum - Fadia Zahra Yuliannisa; Intan Robiatu Solihah; Nursiida Rahmatillah; Deden Abdurahman; Maspuroh (Penerbit Hellow Pustaka, 2025)
This journal examines the meaning and essence of Islamic education curriculum, tracing its underlying concepts and principles. Islamic education curriculum is a planned system aimed at shaping Muslim individuals with noble character, knowledge, and righteous deeds. The journal discusses the definition, principles, components, and content of Islamic education curriculum, as well as integrating theological, anthropological, and ecological values in education. It is expected to serve as a guide for educators in designing effective and meaningful learning processes.